2016
DOI: 10.5194/os-12-1279-2016
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Algal Pigment Index 2 in the Atlantic off the southwest Iberian Peninsula: standard and regional algorithms

Abstract: Abstract. In this study, Algal Pigment Index 2 (API2) is investigated in Sagres, an area located in the Atlantic off the southwestern Iberian Peninsula. Standard results provided by the MEdium Resolution Image Spectrometer (MERIS) ocean colour sensor were compared with alternative data products, determined through a regional inversion scheme, using both MERIS and in situ remote sensing reflectances (R rs ) as input data. The reference quantity for performance assessment is in situ total chlorophyll a (TChl a) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The accuracy of satellite-derived Chl-a for the study region and adjacent Atlantic areas was previously assessed during calibration-validation exercises dedicated to different (standard and alternative) bio-optical algorithms and sensors, including SeaWiFS (Navarro and Ruiz, 2006), MERIS (Cristina et al, 2014(Cristina et al, , 2015(Cristina et al, , 2016a(Cristina et al, , 2016bNechad et al, 2015;Goela et al, 2016b;Tilstone et al, 2017), MODIS-Aqua (Caballero et al, 2014;Sá et al, 2015) and OC-CCI version 1 products (Sá et al, 2015). Overall, these studies indicated that satellite radiometry provides realistic estimates of in situ Chl-a, but usually larger than contemporaneous in situ estimates.…”
Section: Phytoplankton Chlorophyll-a Concentrationmentioning
confidence: 99%
“…The accuracy of satellite-derived Chl-a for the study region and adjacent Atlantic areas was previously assessed during calibration-validation exercises dedicated to different (standard and alternative) bio-optical algorithms and sensors, including SeaWiFS (Navarro and Ruiz, 2006), MERIS (Cristina et al, 2014(Cristina et al, , 2015(Cristina et al, , 2016a(Cristina et al, , 2016bNechad et al, 2015;Goela et al, 2016b;Tilstone et al, 2017), MODIS-Aqua (Caballero et al, 2014;Sá et al, 2015) and OC-CCI version 1 products (Sá et al, 2015). Overall, these studies indicated that satellite radiometry provides realistic estimates of in situ Chl-a, but usually larger than contemporaneous in situ estimates.…”
Section: Phytoplankton Chlorophyll-a Concentrationmentioning
confidence: 99%
“…MLP neural networks have been widely used for a number of applications including performance modeling , job scheduling , load balancing , design space exploration , and OC bio‐optical inversion . A common finding among these studies is that a key to successful MLP applications is empirical tuning of MLP algorithms in terms of network architecture, data pre‐processing, and application‐specific feature selection.…”
Section: Introductionmentioning
confidence: 99%